Impact of Gender Diversity on the Performance of the Companies - Tiwari, Neelu; Sneha (Journal of Commerce and Trade, 2013)
Workforce gender diversity is increasing in countries all over the world (International Labour Office, 2007). For example, women’s representation in the United States civilian labor force has increased from 29.4 percent in 1950 (U.S. Census Bureau, 1970) to 46.3 percent in 2006 (U.S. Bureau of Labor Statistics, 2007). Similarly, women’s representation in the Australian labor force has increased from 22.9 percent in 1954 (Commonwealth Bureau of Census and Statistics, 1958) to 46.1 percent in 2006 (Australian Bureau of Statistics, 2006). The Labor force; female (% of total labor force) in India was last reported at 25.33 in 2010, according to a World Bank report published in 2012. With globalisation and increased competitiveness, gender diversity is now a global voice, not a male voice . A strong emphasis is nowadays being placed on diversity related issues in workplace. Diversity in workplace can be due to various reasons like difference in gender, race, age, national origin etc. But the area of larger concern nowadays is Gender Diversity.This research paper addresses one key question: does gender diversity within corporate management improve performance? As an answer to this question, The Quantitative Research conducted, supports the argument that organizational gender diversity is positively linked to an organization’s performance. The study’s results found a positive relationship between organizational gender diversity and performance when performance was operationalized in terms of profit.